Building on the HIV platform: tackling the challenge of noncommunicable diseases among persons living with HIV. (1st July 2018) - El-Sadr, Wafaa M.; Goosby, Eric
Abstract : N/A: The global HIV response has enabled access to prevention and treatment interventions for millions of people around the world. This investment has enabled the strengthening of health systems, which offers a remarkable opportunity to integrate care for noncommunicable diseases for persons living with HIV who are at risk for or have a noncommunicable disease.